Pengaruh Tingkat Pendidikan terhadap Tingkat Kemiskinan di Indonesia Periode 2015-2023 - Yogi Afrianto (Akuntansi, 2025)
Economic growth in a country can be seen from the level of education and poverty level. The level of poverty in Indonesia affects a person's quality of life. Poverty is caused by lack of education. There are still many people who are not able to get proper access to education, this is not only experienced by people in villages, but also in urban areas. Limited schools, inadequate school facilities, people's access to schools is far and not good, the high cost of education and lack of competence on the part of teachers also make it difficult for people to get a decent education. Of course this has an impact on the level of poverty, low education cannot change a person's ability to be able to compete for their daily needs. The research method in this journal uses a descriptive analysis method sourced from data from BPS from 2015 to 2023. Based on this information, it is found that the level of education influences the level of poverty.